Cavin3 Suppresses Breast Cancer Metastasis via Inhibiting AKT Pathway - An, Xin; Lin, Xi; Yang, Anli; Jiang, Qiwei; Geng, Bingchuan; Huang, Mayan; Lu, Jiabin; Xiang, Zhicheng; Yuan, Zhongyu; Wang, Shusen; Shi, Yanxia; Zhu, Hua (Frontiers in Pharmacology, 2020)
Objective Cavin3 is a putative tumor suppressor protein. However, its molecular action on tumor regulation is largely unknown. The aim of current study is to explore the implication of cavin3 alteration, clinical significance, as well as potential molecular mechanism in regulation of breast cancer. Methods TCGA (The Cancer Genome Atlas), GTEx (Genotype-Tissue Expression) data bases, and 17 fresh paired breast cancer and adjacent normal tissues were analyzed for mRNA levels of Cavin3. Furthermore, 407 primary breast cancer samples were used to determine cavin3 protein expression and clinical significance by using immunohistochemistry, Kaplan Meier analysis and the Cox regression methods. In vitro biological assays were performed to elucidate the function and underlying mechanisms of cavin 3 in breast cancer cells. Results Cavin3 mRNA was dramatically down-regulated in breast cancers compared with normal controls. Among 407 breast cancer patients, 202 (49.6%) patients exhibited undetectable cavin3, and 58 (14.3%) showed decreased expression of cavin3 protein expression (IHC 1+). Loss or reduction of cavin3 correlated with a higher T and N stage, and worse distant metastasis free survival (DMFS) and overall survival (OS). Multivariate survival analysis revealed loss or reduction of cavin3 was an independent fact for worse DMFS. In breast cancer cells, overexpression of cavin3 could inhibit cell migration and invasion, and significantly down-regulated the expression phosphorylated AKT. Conclusion Cavin3 expression is significantly down-regulated in breast cancer, and correlated with distant metastasis and worse survival. Cavin3 functions as a metastasis suppressor via down-regulating Akt pathway, suggesting cavin3 as a potential prognostic biomarker and a target for breast cancer treatment.